Evaluation of early medication persistence with omidenepag isopropyl, a topical selective prostaglandin EP2 agonist, in patients with glaucoma: a retrospective two-institute study - Shunsuke Nakakura; Akiyasu Kanamori; Yuki Nagata; Yasuko Fukuma; Seita Wakabayashi; Miku Adachi (BMJ Open, 2021)
Objectives We evaluated early medication persistence with new topical antiglaucoma eyedrops, omidenepag isopropyl 0.002% (a selective prostaglandin EP2 agonist).Design and setting Retrospective two-institute study in Himeji and Akashi in Japan.Participants We analysed patients with glaucoma who were prescribed topical omidenepag isopropyl from November 2018 to December 2019. From the last outpatient visit of patients until February 2020, 235 patients were prescribed a new solution of omidenepag isopropyl (129 patients in the initial monotherapy group, 85 in the switching group (switched from another topical antiglaucoma eyedrops), 19 added to another topical antiglaucoma eyedrops group, and 2 were lost to follow-up)). Additionally, we recruited 98 patients (3 were lost to follow-up) who received initial latanoprost 0.005% monotherapy during the same period as a control group.Outcomes Medication persistence failure was defined as drug discontinuation due to any adverse effects or change of therapy. Kaplan-Meier survival analysis was performed with a Cox regression analysis.Results Among 233 patients, 48 (20%) showed failure of treatment; the median persistence time of all patients was 165 days, and the median time until discontinuation of omidenepag isopropyl was 45 days. The total persistence rates were 85%, 80% and 70% at 3, 6 and 12 months, respectively. Risk factors for failure were male gender (HR: 1.45, p=0.023) and monotherapy/switching (HR: 1.715, p=0.002). Comparison between latanoprost and omidenepag isopropyl monotherapy, only male gender (HR: 1.43, p=0.016) was a significant risk factor. Failures associated with omidenepag isopropyl were due to insufficient intraocular pressure-lowering efficiency (n=26, observed during all the period), followed by conjunctival hyperaemia (n=10) and visual acuity disturbance (n=5) in patients who were observed until 3 months.Conclusion Medication persistence with omidenepag isopropyl is mostly positive; however, clinicians should also be cautious of early failure.